A Determinan Pendapatan Pelaku UMKM di Kecamatan Candi Kabupaten Sidoarjo - Wahyu Adinda Rizky; Oryza Tannar (Balance : Jurnal Akuntansi dan Bisnis, 2025)
This study aims to analyze the influence of Financial Technology Literacy and People’s Business Credit (KUR) on the Income of MSMEs in Candi District, Sidoarjo Regency. This research uses a quantitative approach with a survey method. The sample consisted of 81 MSME actors selected using the Slovin formula, and data were collected through questionnaires. Data were analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) with the help of SmartPLS 4.0 software. The results show that both Financial Technology Literacy and People’s Business Credit have a positive and significant effect on MSME income. These findings highlight the importance of enhancing digital literacy and improving access to government-supported financing to support income growth among MSMEs.